Credit for the poor: the case of BRAC in Bangladesh - Chowdhury, AMR; Mahmood, M; Abed, FH (BRAC, 2019)
As the rural population of Bangladesh increases, landlessness among people once dependent upon agriculture is a growing problem. The Bangladesh Rural Advancement Committee (BRAC) has been working with the rural poor since 1972, and in 1979 it began to provide credit via its 81 branches through the Rural Development Programme (RDP). Ten years later the success of the RDP in generating incomes and employment through small businesses and building up assets has been evaluated, and this article describes the results of the evaluation.